CARDIOPROTECTIVE ROLES OF THE CHINESE MEDICINAL FORMULA BAO-XIN-TANG ON ACUTE MYOCARDIAL INFARCTION IN RATS - Wang, Yang; Wang, Weihao; Peng, Weijun; Liu, Weiping; Cai, Weijun; Xia, Zian; Zhang, Honggeng; Xing, Zhihua (African Journal of Traditional, Complementary and Alternative Medicines, 2017)
Background: Bao-Xin-Tang (BXT) is a traditional Chinese medicinal formula used for the treatment of coronary heart disease andknown to have favorable therapeutic benefits. The current study was designed to determine whether BXT has a cardioprotective rolefor acute myocardial infarction. The underlying mechanisms were also explored.Materials and Methods: The Sprague-Dawley rat model of acute myocardial infarction was established by occluding the left anteriordescending branch of the coronary artery. After a 3-h ischemic period, we determined the myocardial infarction size, inflammatorycomponents, and antioxidant activities.Results: The data showed that BXT could reduce the infarction size and lower the levels of C-reactive protein, interleukin-6, andmyeloperoxidase, and increase the activities of superoxide dismutase and the anti-inflammatory cytokine, interleukin-10. These resultsindicate that administration of BXT, following acute myocardial infarction, could reduce infarct size.Conclusion: The effects of BXT may be related to its anti-inflammatory and anti-oxidative properties.